Dengue Fever Presenting as Acute Pancreatitis: A Case Series - Khanal, Kishor; Poudel, Saroj; Ghimire, Anup; Regmi, Ashim; Bhattarai, Rashmita; Pandey, Aakash (Journal of Advances in Internal Medicine, 2023)
Acute pancreatitis (AP) is a rare complication of Dengue fever with unpredictable progression and outcome. There have been increasing reports of acute pancreatitis due to dengue. Fever, abdominal pain or tenderness are the presenting clinical manifestations on hospital admission. We reported two similar cases of Dengue who presented with the complaints of fever, abdominal pain, and generalized body ache. Acute pancreatitis was diagnosed in both cases following blood investigations, ultrasound and contrast enhanced computed tomography (CECT) of the whole abdomen.